Feasibility and Value of the Critical View of Safety in Difficult Cholecystectomies. Issue 4 (April 2019) - Felli, Emanuele; Mascagni, Pietro; Wakabayashi, Taiga; Mutter, Didier; Marescaux, Jacques; Pessaux, Patrick
Abstract : Supplemental Digital Content is available in the text